Several uncertainty principles for two-step nilpotent Lie groups - Pengcheng, Niu; Tang Sufang (Հայաստանի ԳԱԱ)
Some Hardy׳s uncertainty principles are proved for two-step nilpotent Lie groups. The group Fourier transforms are considered.
Keywords: Mathematics; Science